2008
DOI: 10.1007/s00415-008-0985-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in multiple sclerosis

Abstract: The RNFL measured by OCT may be useful as a surrogate marker for assessment of brain atrophy in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
56
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(75 citation statements)
references
References 22 publications
13
56
1
Order By: Relevance
“…The investigators have found that in MS, RNFL thickness measured by optical coherence tomography is associated with parenchymal fraction of the brain, cerebral fluid volume, and MS lesion volume [18,19,20]. RNFL thickness was also significantly correlated with fractional anisotropy and radial diffusivity of the connected contralateral optic radiation [21].…”
Section: Discussionmentioning
confidence: 99%
“…The investigators have found that in MS, RNFL thickness measured by optical coherence tomography is associated with parenchymal fraction of the brain, cerebral fluid volume, and MS lesion volume [18,19,20]. RNFL thickness was also significantly correlated with fractional anisotropy and radial diffusivity of the connected contralateral optic radiation [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been reported that RNFL thinning is associated not only with demyelinating diseases involving optic nerve such as multiple sclerosis but also with primary neurodegenerative disorders in which visual deficits are less relevant [8,9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…Petzold A et al [14] meta-analyzed 12 studies regarding RNFL in eyes with multiple sclerosis optic neuritis (MS ON) [12,[15][16][17][18][19][20][21][22][23][24] . They observed significant average RNFL loss -20.38 µm in MSON eyes (95% CI, -22.86 to -17.91).…”
Section: Discussionmentioning
confidence: 99%